The concept of motivation and the unity of a human subject in Schopenhauer’s “On the freedom of the will” - Ustyniak, Iwo (Hybris, 2015)
In the following article I am going to present the detailed analysis of the concept of motivation in philosophy of Arthur Schopenhauer. It will be particularly important for me to present this concept in relation to the problem of identity of two aspects of human subject: cognitive and volitional. Moreover I will show that there are at least several important problems and obscurities connected with Shopenhauer’s standpoint even though his concept of action is unquestionably close to our “natural” and “common sense” beliefs.